Nickel-catalyzed straightforward and regioselective C-H alkenylation of indoles with alkenyl bromides: scope and mechanistic aspect - Jagtap, Rahul A.; Vinod, C. P.; Punji, Benudhar (ACS Catalysis, 2019)
Nickel-catalyzed regioselective C-H bond alkenylation of indoles and related heteroarenes with alkenyl bromides is accomplished under relatively mild conditions. This method allows the straightforward synthesis of C-2 alkenylated indoles employing an air-stable and well-defined nickel catalyst, (bpy)NiBr2, providing a solution to the limitations associated with hydroindolation and oxidative alkenylation. The reaction conceded the coupling of indole derivatives with various alkenyl bromides, such as aromatic and heteroaromatics, alpha- and beta-substituted as well as exo- and endo-cyclic alkenyl compounds. An extensive mechanistic investigation, including controlled study, reactivity experiments, kinetics and labeling studies, and EPR and XPS analyses, highlights that the alkenylation proceeds through a single-electron transfer process comprising an odd-electron oxidative addition of alkenyl bromide. Furthermore, the alkenylation operates via a probable Ni(I)/Ni(III) pathway involving the rate-limiting C-H nickelation of indole.
Keywords: alkenylation; C-H activation; indoles; Mechanism; Nickel; single-electron transfer